Κ-carrageenan/chitosan nanolayered coating for controlled release of a model bioactive compound - Pinheiro, A. C. (2012)
Multilayer nanocoatings composed of K-carrageenan, a sulphated anionic polysaccharide, and chitosan, a cationic polysaccharide, were produced by layer-by-layer deposition. The model cationic compound Methylene Blue (MB) was incorporated in different positions of the nanolayered coating and its loading and release behavior was evaluated. UV-VIS spectroscopy and quartz crystal microbalance analysis showed that the amount of MB loaded increased with the distance from the first layer, suggesting that the MB was able to diffuse into the K-carrageenan/chitosan nanolayered coating and not only adhered to the surface of the layer immediately below it. For most of the tested conditions, the MB release from the K-carrageenan/chitosan nanolayered coatings was successfully described by the linear superimposition model, which allowed concluding that MB transport is due to both concentration gradient and the polymer relaxation of the nanolayers. However, depending on temperature and pH of the medium and on the position of MB incorporated on the nanolayered coatings, different mechanisms prevail.Industrial relevance: The development of novel edible coatings with improved functionality and performance for e.g. fresh and minimally processed fruits is one of the challenges of the post-harvest industry. This work contributes to the understanding of the loading and release phenomena involved in structures at the nanoscale, which is useful for the development of bioactive compounds release systems for application in food industry. Moreover, the K-carrageenan/chitosan nanolayered coatings represent a promising platform from which the controlled release of different bioactive compounds may be explored.